Birth weight and cognition in children with epilepsy. Issue 6 (15th April 2014) - Jackson, Daren C.; Lin, Jack J.; Chambers, Karlee L.; Kessler‐Jones, Alanna; Jones, Jana E.; Hsu, David A.; Stafstrom, Carl E.; Seidenberg, Michael; Hermann, Bruce P.
Summary Objective Birth weight is an important indicator of prenatal environment, and subtle variations of birth weight within the normal range have been associated with differential risk for cognitive and behavioral problems. Therefore, we aimed to determine if there are differences in birth weight between full‐term children with uncomplicated new/recent‐onset epilepsies and typically developing healthy controls. We further examined the relationships between birth weight and childhood/adolescent cognition, behavior, and academic achievement. Methods One hundred eight children with new‐onset/recent‐onset epilepsy and 70 healthy controls underwent neuropsychological assessment. All participants were born full‐term (>37 weeks) without birth complications. Parents were interviewed regarding their child's gestation, birth, and neurodevelopmental history. Results Birth weight of children with epilepsy was significantly lower than healthy controls (p = 0.023). Whereas birth weight (covaried with age, sex, handedness, and mother's education) was significantly associated with cognition in controls in multiple domains (intelligence, language, aspects of academic achievement), this relationship was absent in children with epilepsy. Birth weight was not associated with clinical epilepsy variables (age of onset, epilepsy syndrome) and was not predictive of a variety of other academic or psychiatric comorbidities of epilepsy. Significance Although the origin of lower birth weight in children with epilepsy is unknown, these findings raise the possibility that abnormal prenatal environment may affect childhood‐onset epilepsy. Furthermore, the positive relationship between birth weight and cognition evident in healthy controls was disrupted in children with epilepsy. However, birth weight was not related to academic and psychiatric comorbidities of childhood epilepsy. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.